Factors associated with lack of postnatal care among Palestinian women: A cross-sectional study of three clinics in the West Bank - Maxwell Annette E; Mikolajczyk Rafael T; Dhaher Enas; Krämer Alexander (BMC, 2008)
Abstract Background Only about one-third of women in Palestine (West Bank and Gaza) obtain postpartum care. Therefore, the goal of this study was to assess factors associated with lack of postnatal care, women's reasons for not obtaining postnatal care, and their attitudes towards its importance. Methods In early 2006, a cross-sectional survey was conducted at three clinics run by the Ministry of Health providing Mother and Child Health Care in West Bank, Palestine. A total of 264 postpartum women attending the clinics were interviewed face-to-face, using a structured questionnaire. Results Although the majority of women considered postnatal care necessary (66.1%), only 36.6% of women obtained postnatal care. The most frequent reason for not obtaining postnatal care was that women did not feel sick and therefore did not need postnatal care (85%), followed by not having been told by their doctor to come back for postnatal care (15.5%). Based on a multivariable analysis, use of postnatal care was higher among women who had experienced problems during their delivery, had a cesarean section, or had an instrumental vaginal delivery than among women who had a spontaneous vaginal delivery. Use of postnatal care was also higher among women who delivered in a private hospital as compared to those who delivered in a public hospital. In addition, we found regional differences. Conclusion The higher use of postnatal care among high-risk women is appropriate, but some clinically dangerous conditions can also occur in low-risk women. Future efforts should therefore focus on providing postnatal care to a larger number of low-risk women.